Advanced malignant lung disease: what the specialist can offer - Gompelmann, Daniela; Eberhardt, Ralf; Herth, Felix (Respiration, 2011)
Lung cancer is not only the most commonly diagnosed cancer worldwide, but it is still the leading cause for cancer-related death. The 5-year survival for lung cancer in Europe and in the USA is totally 16%. Therefore, a palliative therapy regimen is required to control the disease and reduce symptoms with the objective of enhancing quality of life of lung cancer patients. In addition to chemotherapy that is still one of the most important pillars in the treatment of advanced lung cancer, further interventional strategies can be offered to improve a patient’s quality of life. A locoregional tumour progression is frequently associated with malignant pleural effusion or pericardial effusion, central airway obstruction, tracheo-oesophageal fistula, severe haemoptysis or superior vena cava (SVC) syndrome threatening life and necessitating urgent palliation. Recurrent pleural effusion causing dyspnoea can be managed by pleurodesis, serial thoracocentesis or insertion of an indwelling catheter. Symptomatic malignant pericardial effusion often requires an urgent pericardiocentesis. Furthermore, surgical procedures, instillation of sclerosing agents or local chemotherapy should be considered in refractory pericardial effusion. The therapy regimen of central airway stenosis includes mechanical and thermic endoscopic procedures providing rapid relief of symptoms. To prevent recurrence of airway obstruction, the insertion of a stent or palliative brachytherapy provide re-establishment of the patency of obstructed airways. Haemoptysis can be managed by bronchoscopic interventions as well as by arterial embolization or palliative thoracic radiotherapy. The therapy of SVC syndrome is dependent of histology. In small-cell lung cancer, chemotherapy is recommended. In non-small-cell lung cancer, stent insertion and/or radiotherapy are the therapeutic pillars.